Manajemen Pengelolaan Infaq pada BAZNAS (Studi Deskriptif 2015-2016) - Subhan Subhan (Indonesian Journal of Islamic Economics and Business, 2018)
Infaq is one of instrumen of islamic social finance, it has a significant role in islamiceconomics development. This study aims to describe the role of infaq in indonesia byanalyzing the management of infaq at the National Zakat Agency BAZNAS as legalauthority in collecting and distributing infaq in Indonesia. This study uses a researchmethod that is descriptive analysis-comparative, which describes data related to infaqmanagement at BAZNAS. Data analysis stages consist of data reduction, datapresentation and drawing conclusions. The management of Infaq funds at BAZNAS is inaccordance with the applicable law, with a separate recording system separate from zakatand other alms. It also collaborates with UPZ in mosques to optimize the collection anddistribution of infaq.